SOME TOPOGRAPHICAL AND HISTOLOGICAL STUDIES OF THYROID AND PARATHYROD GLANDS OF MOORHEN (Gallinula c. chloropus) - Kadhim, K.K.; Al-Samarrae, N.S.; Al-Fayas, J.Y. (The Iraqi Journal of Veterinary Medicine, 2021)
The thyroid gland of Moorhen has two separated lobes. These lobes were located in the throracic inlet and receive blood supply from the cranial, middle and caudal thyroid arteries.The histological organization of the thyroid gland in Moorhen is surrounded by a distinct connective tissue capsule and the parenchymal cells were arranged into colloid filled follicles enmeshed in the highly vascular interstitial connective tissue. The bilaterally paired, round to oval, parathyroid glands in Moorhen were located intrathoracically near or close to the caudal pole of the thyroid glands. They receive blood by short branches from caudal thyroid artery and small branch from the common carotid artery.The parathyroid glands in Moorhen have a thin connective tissue capsule. Its parenchymal cells were arranged into an irregular, anastomosing cords of chief cells. No oxyphil cells were found in the parathyroid glands of Moorhen.